Renormalized Solutions for Nonlinear Degenerate Elliptic Problems with L1 Data - Ammar, Kaouther; Redwane, Hicham (Revista Matemática Complutense, 2009)
We are interested in a class of nonlinear degenerate diffusion problems with a diffusion function a(x, u, Vu) which is not controlled with respect to u and which is not uniformly coercive on the weighted Sobolev spaces W1,p0 (Ω, w). Existence of a renormalized solution is proved in the L1-setting.